2017
DOI: 10.1039/c6ay02984a
|View full text |Cite
|
Sign up to set email alerts
|

An LC-MS/MS method for the determination of 28 polar environmental contaminants and metabolites in vegetables irrigated with treated municipal wastewater

Abstract: An analytical method for the determination of wastewater-derived contaminants and possible metabolites in common plant tissues was developed and validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Further, P. australis metabolized the carbamazepine-10,11-epoxide into 9-acridine carboxaldehyde, which is analogous to other studies [ 28 , 31 , 32 ]. The 9-acridine carboxaldehyde is a reactive compound that was identified in leaf, rhizome and root extracts of plants exposed to 10 and 50 µM carbamazepine.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Further, P. australis metabolized the carbamazepine-10,11-epoxide into 9-acridine carboxaldehyde, which is analogous to other studies [ 28 , 31 , 32 ]. The 9-acridine carboxaldehyde is a reactive compound that was identified in leaf, rhizome and root extracts of plants exposed to 10 and 50 µM carbamazepine.…”
Section: Discussionsupporting
confidence: 84%
“…In CBZ incubation, different transformation products were identified, which originated from different metabolism pathways (PCM). The 10,11-diOH pathway (PCM) has been investigated comprehensively in plants like cucumber, tomato, sweet potato, lettuce, carrot and horseradish [ 28 , 31 ]. The main transformed product is carbamazepine-10,11-epoxide (Martínez-Piernas et al, 2019), which has been identified in leaf, rhizome and root in both incubations levels 10 and 50 µM, as shown in Table S3 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of 28 target compounds (Table S1) from plant samples was performed by solid–liquid extraction (SLE). Method details are published elsewhere . In brief, 0.5 g of freeze-dried plant material was extracted with 5 mL of methanol and sonicated for 20 min followed by shaking for 30 min.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…As an example, reclaimed wastewater counts for 50% of the total irrigation water used in Israel and also within the European Union, countries like Spain or Italy use substantial amounts of reclaimed water . For this reason the uptake, translocation and metabolization of xenobiotics by plants is the topic of a series of research projects reflected in a number of corresponding publications .…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the studies published so far, most of them can be categorized into two major groups, one of them devoted to the (ultra)‐trace analysis of the parent drug sometimes together with one or two of its major metabolites, and a second group dealing with the identification of metabolites produced in the plant upon treatment with (mostly higher concentrations) of the active pharmaceutical ingredients (API). Examples from the first group are the analysis of several pharmaceuticals in lettuce , the determination of 28 environmental contaminants (including several API´s) in lettuce, cabbage and tomato or investigations on the uptake of 19 common pharmaceuticals by celery, lettuce, cabbage, spinach, carrot, cucumber, bell pepper and tomato under field conditions . Studies devoted to the elucidation of the metabolization of the API´s by plants have for example focused on the transformation of carbamazepine in plant roots , or in tomato plants , on conjugation of amino acids with API´s , or on the metabolization of four non‐steroidal anti‐inflammatory drugs (NSAIDs) in cress .…”
Section: Introductionmentioning
confidence: 99%